Meclofenamate elicits a nephropreventing effect in a rat model of ischemic acute kidney injury by suppressing indoxyl sulfate production and restoring renal organic anion transporters - Saigo C; Nomura Y; Yamamoto Y; Sagata M; Matsunaga R; Jono H; Nishi K; Saito H (Drug Design, Development and Therapy, 2014)
Chika Saigo,1 Yui Nomura,1 Yuko Yamamoto,1 Masataka Sagata,1 Rika Matsunaga,1 Hirofumi Jono,1,2 Kazuhiko Nishi,3 Hideyuki Saito1,2 1Department of Clinical Pharmaceutical Sciences, Graduate School of Pharmaceutical Sciences, Kumamoto University, 2Department of Pharmacy, Kumamoto University Hospital, 3Department of Hemo-Dialysis, Kumamoto University Hospital, Kumamoto, Japan Abstract: Indoxyl sulfate (IS), a putative low-molecular weight uremic toxin, is excreted in the urine under normal kidney function, but is retained in the circulation and tissues during renal dysfunction in acute kidney injury and chronic kidney disease. IS, which is one of the most potent inducers of oxidative stress in the kidney and cardiovascular system, is enzymatically produced in the liver from indole by cytochrome P450-mediated hydroxylation to indoxyl, followed by sulfotransferase-mediated sulfate conjugation. We used rat liver S9 fraction to identify inhibitors of IS production. After testing several compounds, including phytochemical polyphenols, we identified meclofenamate as a potent inhibitor of IS production with an apparent IC50 value of 1.34 µM. Ischemia/reperfusion (I/R) of rat kidney caused a marked elevation in the serum IS concentration 48 hours after surgery. However, intravenous administration of meclofenamate (10 mg/kg) significantly suppressed this increase in the serum level of IS. Moreover, IS concentrations in both kidney and liver were dramatically elevated by renal I/R treatment, but this increase was blocked by meclofenamate. Serum creatinine and blood urea nitrogen were markedly elevated in rats after renal I/R treatment, but these increases were significantly restored by administration of meclofenamate. Renal expression of both basolateral membrane-localized organic anion transporters rOAT1 and rOAT3 was downregulated by I/R treatment. However, expression of rOAT1 and rOAT3 recovered after administration of meclofenamate, which is associated with the inhibition of I/R-evoked elevation of prostaglandin E2. Our results suggest that meclofenamate inhibits hepatic sulfotransferase-mediated production of IS, thereby suppressing serum and renal accumulation of IS. Meclofenamate also prevents the prostaglandin E2-dependent downregulation of rOAT1 and rOAT3 expression. In conclusion, meclofenamate was found to elicit a nephropreventive effect in ischemic acute kidney injury. Keywords: uremic toxins, hepatic sulfotransferase, renal ischemia/reperfusion, renal tubular cell